PENGARUH STRATEGI KEMANDIRIAN TERHADAP MINAT BELAJAR ANAK TUNA DAKSA - Hasanah, Sivaul; Sri Kantina; Agustin Wijaya, Reynata; Fadkhulillah, Nur Nizza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Children with physical disabilities often face mobility challenges and self-confidence issues that negatively impact their learning interest. This study aims to analyze the effect of implementing independence strategies on enhancing the learning interest of children with physical disabilities. The study employed a quantitative approach with a one-group pretest–posttest pre-experimental design. The participants consisted of 15 elementary school students in an inclusive education setting. Data were collected through questionnaires and observations, then analyzed using a paired sample t-test. The results showed a significant increase in students' learning interest following the intervention. These findings indicate that independence strategies have a positive influence on students' motivation, self-confidence, and engagement in learning. Therefore, independence strategies are recommended as an effective approach to support inclusive education practices for students with physical disabilities.